2022
DOI: 10.3390/polym14122382
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Potential Effects of Ultra-Short Laser-Textured Porous Poly-ε-Caprolactone Scaffolds on Bacterial Adhesion and Bone Cell Metabolism

Abstract: Developing antimicrobial surfaces that combat implant-associated infections while promoting host cell response is a key strategy for improving current therapies for orthopaedic injuries. In this paper, we present the application of ultra-short laser irradiation for patterning the surface of a 3D biodegradable synthetic polymer in order to affect the adhesion and proliferation of bone cells and reject bacterial cells. The surfaces of 3D-printed polycaprolactone (PCL) scaffolds were processed with a femtosecond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Notably, the PCL/ZIF-8@CCM shows a lower inhibition rate, which might be attributed to the bacterial adsorption and nonantibacterial feature of pure PCL. 57,58 These results indicate that the loading of ZIF-8@CCM endows the fiber membranes with a higher antibacterial activity. With both excellent PM removal performances and antibacterial activity, the ZIF-8@CCM-loaded fiber membrane provides an ideal fibrous filter.…”
Section: Pm Removal Performances Of the Zif-8@ccm Composite Nanofiber...mentioning
confidence: 89%
“…Notably, the PCL/ZIF-8@CCM shows a lower inhibition rate, which might be attributed to the bacterial adsorption and nonantibacterial feature of pure PCL. 57,58 These results indicate that the loading of ZIF-8@CCM endows the fiber membranes with a higher antibacterial activity. With both excellent PM removal performances and antibacterial activity, the ZIF-8@CCM-loaded fiber membrane provides an ideal fibrous filter.…”
Section: Pm Removal Performances Of the Zif-8@ccm Composite Nanofiber...mentioning
confidence: 89%
“…Filipov et al used a femtosecond laser to surface 3D printed PCL to produce microchannels and microprojections on the surface of the implant. 99 The microtopography had a good antibacterial effect on S. aureus while promoting the growth of MG63 cells. Chan et al performed laser surface treatment on three commonly used orthopedic metal materials using a fiber laser at the NIR wavelength of 1064 nm.…”
Section: Direct Contact Antimicrobial Scaffoldmentioning
confidence: 95%
“…No thermally-induced collateral damage could be observed. In previous research of our group, Filipov et al developed microstructures of similar morphology and dimensions on 3D printed PCL and investigated their effects on the adhesion of osteoblastic-like cells [10]. The authors found that the cells adhered preferably to the structured surfaces and not on untreated smooth scaffolds.…”
Section: Development Of Surface Micropatterns For Enhanced Cell Attac...mentioning
confidence: 99%